QUALITY IMPROVEMENT METHODOLOGY IN GENERAL EDUCATION SCHOOLS - Paluaniyazova Tamara Hamidullaevna (Journals Park Publishing, 2022)
The article is devoted to improving the quality of teaching in schools. The starting idea for improving the situation is the orientation of postgraduate education to the individual professional needs of the teacher, related to achieving the best result of professional activity. In this regard, the problem of improving the quality of education is considered by the author through the activities of professional learning communities of teachers (professional learning communities). The analysis of foreign sources shows the possibilities of professional learning communities. The given data of the experimental practice of the activities of professional learning communities testify to the positive experience of schools in organizing the process of teaching teachers in direct professional practice. In the article, the authors propose steps to create professional learning communities of teachers: analysis of educational outcomes and identification of children's learning difficulties, selection of effective pedagogical strategies (technologies), analysis of teachers' readiness to implement the chosen strategy and identification of teachers' professional deficits, joint design of the content of the activities of a professional learning community. In conclusion, conclusions are drawn about the external and internal conditions for the activity of professional learning communities.
Keywords: professional communities of teachers, professional development of a teacher, schools, unfavorable social conditions.